Survey data of a traditional communal water irrigation system in Northern Thailand - Arriya Mungsunti; Kevin A. Parton; Arief Anshory Yusuf; Tossapond Kewprasopsak (Data in Brief, 2022)
This data article contains a description of a dataset collected by a survey on a traditional communal water irrigation system. This is the Muang fai, a 700-years old communal irrigation system in Northern Thailand. The Muang fai is managed through a series of regulations that are close to Ostrom's principles of effective common property resources (Ostrom, 1990). The survival of this long-standing practice, including its knowledge of the water-flow characteristics of the watershed, is under threat as new technologies, such as groundwater pumping, become increasingly accessible. The target population of the survey was the group of Longan farmers who are located within the 12 villages that are engaged in Muang fai Sop Rong in Chiang Mai Province, Northern Thailand. Information was specifically collected about irrigation practices, farmland characteristics and socio-economic variables from 570 longan (their main crop) farmer households. Roughly half of these sampled farmers practise Muang fai, the other half practise underground pumping irrigation. The irrigation information collected includes type of irrigation (surface or underground), the quantity of water used, pumping methods (if pumps are used). Farming characteristics collected include volume and value of the harvests, land size, and distance to irrigation canal. Socioeconomic characteristics included among others: farmers’ income, expenditure, education, off-farm employment and Muang-fai membership. This dataset can be a source of baseline information for future research as well as help preserve the knowledge of this tradition.